The Correlation of Parents Height Characteristics and Maternal Nutritional Status During Pregnancy Based on Upper Arm Circumference (UAC) and Stunting Incidence of Toddlers Aged 24-59 Months in the Working Area of Berbek Community Health Center Nganjuk Regency - Wahyu Nuraisya; Wahyu Erdi (STIKes Patria Husada Blitar, 2021)
Stunting in Indonesia was the fifth ranks in the world, influenced by many factors, some of which are the height of the parents and the nutritional status of the mother during pregnancy. The purpose of this research was to determine the correlation of parent height characteristics and maternal nutritional status during pregnancy based on Upper Arm Circumference (UAC) with stunting incidence in toddlers aged 24-59 months in the working area of the Berbek Public Health Center Nganjuk Regency. The research design used correlation analytic research design with observational method with case control approach. The independent variables consisted of parental height characteristics and maternal nutritional status during pregnancy based on UAC, and the dependent variable was stunting incidence. The population was 2266 respondents of under-five children aged 24-59 months. The sampling technique used quota sampling consisted 96 respondents. The instrument used height measurement tool, the Mother's Child Health book and the Public Health Center Weigh Activity Report, 2011. This research was conducted from 22 July to 22 August 2019 in three selected villages namely Sumberurip, Sumberwindu and Semare villages. Data analysis used chi-square test Î± (0.05). The results showed that almost all mothers and fathers had normal height characteristics, almost all respondents had the nutritional status of the mother during normal pregnancy. Analysis of height, circumference of the mother, and nutritional status of the mother during pregnancy based on Upper Arm Circumference (UAC) was obtained Ï value = 0.036; 0,000 and 0,000 <Î± 0,05. It meant that there was a correlation between parental height characteristics and maternal nutritional status during pregnancy based on Upper Arm Circumference (UAC) with the incidence of stunting in children aged 24-59 months in the Berbek Public Health Center Nganjuk Regency Parental height and nutritional status of the mother during normal pregnancy, it will have the opportunity to have a child with good growth.